Determinan Agresivitas Pajak Sub-sektor Konstruksi Bangunan, Properti, dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024 - Ayu Putri Lestari; Heri Yanto (Universitas Sains dan Teknologi Komputer, 2026)
This study aims to analyze the determinants of tax aggressiveness in construction, property, and real estate companies listed on the Indonesia Stock Exchange (IDX) during 2021–2024. The sample consists of 80 companies with 220 observations, selected using purposive sampling based on criteria such as the availability of financial statements and the absence of losses during the research period. The variables include tax aggressiveness (ETR), profitability (ROA), leverage (DAR), board size, and firm size (SIZE). Data were analyzed using PLS-SEM with WarpPLS 8.0. The results show that profitability has a negative and significant effect on tax aggressiveness, while leverage has a positive and significant effect. Board size does not significantly affect tax aggressiveness but positively influences profitability and leverage. Firm size negatively affects profitability but positively impacts board size and leverage. These findings indicate that financial factors are more dominant in determining tax aggressiveness than board size, a corporate governance mechanism